Hazards of heat exposure. A review. - Dukes-Dobos, Francis N (Scandinavian Journal of Work, Environment & Health, 1981)
The usefulness of the various heat stress standards recommended by occupational health authorities in the United States is discussed from the point of view of their effectiveness in preventing acute heat illnesses. In this connection, the findings from an investigation of four recent fatal industries heat casualties are described. A review is presented of the recent literature on acute occupational heat illnesses. Also reviewed is the information on chronic heat illnesses. Most of this latter data comes from studies performed in Europe and South America. However, a recent mortality study among steel workers in the United States contributed significantly to the knowledge of this problem area. This study found the primary targets of chronic heat illnesses to the cardiovascular and the gastrointestinal systems, although there was some evidence that the reproductive functions may be affected. A discussion on how to prevent heat illnesses is presented.
Keywords: acute heat illness; cardiovascular disease; chronic heat illness; exposure; gastrointestinal disease; hazard; heat; heat exhaustion; heat exposure; heat stress; heat stress standard; heat stroke; mortality; permissible exposure limit to heat; review; steel worker; steel worker mortality; threshold limit value